A new old Damascus : authenticity and distinction in urban Syria - Salamandra, Christa (Indiana series in Middle East studies., 2004)
"[F]illed with rare encounters with Syria's oldest, most elite families. Critics of anthropology's taste for exoticism and marginality will savor this study of upper-class Damascus, a world that is urbane and cosmopolitan, yet in many ways as remote as the settings in which the best ethnography has traditionally been done ... [Written] with a nuanced appreciation of the cultural forms in question and how Damascenes themselves think, talk about, and create them."--Andrew ShryockIn contemporary urban Syri